The Role of Community Police in Crime Prevention and Control for the Effective Management - Rachel Nimma Ndakotsu (International Studies Journal)
The study examined community policing and crime prevention in Nigeria with reference to Jenkwe Development Area. The study further sought to achieve other objectives which include to identify community policing and crime prevention; to examine the duration of combatting crimes; to identify the problems with community policing and crime prevention. The study adopted survey design and took census of the entire target population of the three communities. Questionnaire was administered. Tables, frequency and percentages were used to describe the responses from respondents, which shows that 3.56% was targeted sample from the population, out of 46 of the respondents, representing 29.5% described community policing as very effective mechanism of crime prevention in the study area. As well out of 45 respondents, 28 of the respondents representing 62.22% agreed quality information determined police response on crime prevention, this implies that community policing is an appropriate tool for crime prevention. While chi-square was used to examine the relationship between and among the variables and test of hypotheses. On this basis of analysis for this study, the study revealed that community policing and crime prevention has strengthen relationships of the community and the police amongst others. The study further revealed that community policing and crime prevention faces inadequate funding, lack of enough physical structures, poor management and logistics to be some of the major problems affecting community policing and crime prevention. The study concluded and recommended that community policing and crime prevention should be adequately funded to acquire state of the arts equipment’s to enhance effective community policing and crime prevention, also the police should create awareness for everyone to provide useful and needful information.